Идентификация и образ адресата в интернет-соболезнованиях - Andrzej Narloch (Studia Rossica Posnaniensia)
An internet condolence letter has become a new form of communication in special circumstances. The selection of appropriate vocabulary plays a vital role in writing internet condolence letters as it is indirectly connected with expressing sympathy, support and understanding. In addition, the form of addressing the recipient often determines the right reception of a condolence letter. A recipient is identified in apostrophes in many ways. His or her nationality is emphasized most frequently. Also, ethnicity and social relationships are quite often indicated. Very emotional apostrophes directed to the dead have also been found in the analyzed material. Each kind of identification requires using suitable means of expression. Many of them contain additional emotive language. The analyzed apostrophes are very emotional and full of positive evaluative expressions. All the same, there are also many official, almost pompous constructions.